Prevalence of mealybug wilt disease of pineapple and the associated viruses - Nyarko, Joseph (University of Cape Coast, 2019)
The study assessed the awareness of mealybug wilt of pineapple (MWP) farmers and their disease management practices in the Komenda-Edina-Eguafo-Abirem (KEEA), Abura-Asebu-Kwamankese (AAK), and Ekumfi districts in the Central Region of Ghana. The study also surveyed the incidence and severity of the MWP disease in pineapple fields across the three districts in 2018. Household data were collected using structured questionnaire from 180 respondents and analysed using descriptive and inferential statistics. Incidence and severity scores of MWP disease were determined from twenty (20) pineapple farms selected from each of the three districts. The field data was subjected to analysis of variance (ANOVA) and the means separated with least significant difference (LSD) method at P<0.05. The majority of the farmers (88.9%) had knowledge on the existence of the disease in their farms and its effect on yield. Majority of farmers used their own planting materials (59.4%), practice monocropping (67.8%), do not apply any fertilizer (78.9%), do not manage the disease on their farms (58.4%), fallow plots (63.9%) and mother plots (55.6%). Incidence of MWP disease differed significantly between pre- and post-induction growth stages and among the three districts (p<0.05), ranging from 2.20±0.46 to 9.45± 1.10%. Soil fertility status of the farms was inherently low. Five qRT-PCR assays with pineapple mealybug wilt associated virus (PMWaVs) species specific primers successfully detected five species of PMWaVs, namely PMWaV-1, PMWaV-2, PMWaV-3, PMWaV-4 and PMWaV-5, with abundance of mixed infections. Phylogenetic analyses with 15 sequenced isolates from the study and some published sequences from GenBank, confirmed the presence of PMWaV-1, -2 and -3 in the Central region.
xvi,142p:,ill.
Keywords: Farmers; Incidence; Mealybug wilt of pineapple; Prevalence; RNA extractio; Virus